Attitudes and Perceptions Towards Cultured Meat Among General Population in Pakistan - Muhammad Ahsan; Muhammad Uzair; Moazzam Ali (ASEAN Journal of Science and Engineering Education, 2022)
Meat demand and production are under strain because of their effect on the atmosphere, animal welfare, and the growing demand for proteins worldwide. Cultured meat (CM) is now an industry, politics, and society's hot subject. While understanding of the effects is on the rise, opposition to the removal of meat from our diets remains. One alternative way of alleviating these consequences is by producing in vitro meat. A pre-coded questionnaire was used to poll the Pakistani population on their views and acceptance of laboratory-cultured meat. The acceptance of CM among the Pakistani population was poor at 27.1%. About one-third of the respondents showed positive attitudes and concerns towards CM and were willing to consume in vitro meat and its substitute products. Participants were more sensitive, concerning its safety, ethical issues, nutritional value, and other health-related concerns. Since the Pakistani population was less likely to accept CM, the government and stakeholders should address this problem through media campaigns and clear people's misconceptions regarding its safety and ethical concerns for the preservation of the environment and meeting the demand for protein.